A Restorative Justice Intervention in United States Prisons: Implications of Intervention Timing, Age, and Gender on Recidivism - Richner, Kailey A. (International journal of offender therapy and comparative criminology, 2023)
Restorative justice seeks to balance the needs of the victim, offender, and community by repairing the harm caused by crime and wrongdoing and improving the prosocial competencies and accountability of the offender in response to an offense. Restorative justice interventions (RJIs) offer an alternative method to reduce harm and short- and long-term recidivism. However, empirical validation of mechanisms and moderating factors warrant additional inquiry within jail and prison settings. Thus, the authors sought to examine RJI delivery timing on recidivism outcomes with age and gender as moderators. A final sample of 1,316 individuals (49.8% female) incarcerated in several United States prisons received an RJI between 2001 and 2017. RJI timing did not relate to binary recidivism. However, women recidivated less than men and older individual recidivated less than younger individuals. For the subsample of reoffenders (n = 283), RJIs delivered closer to release increased the amount of time before recidivism. Delivering RJIs closer to release from prison may allow for other community programs to intervene and reduce recidivism even further.